Pemberdayaan Mahasiswa Magang dalam Proyek Pembangunan Laboratorium Terpadu Kemaritiman Universitas Negeri Gorontalo - Saman, Satar; Kaharu, Anton; Dali, Faiza A.; Husain, Rahim; Idji, Berni; Dunggio, Mohamad Faisal (Yayasan Daarul Huda Kruengmane, 2025)
The construction of the Integrated Maritime Laboratory, funded through the 2024 State Sharia Securities (SBSN) budget, serves not only as a means of developing educational infrastructure but also as a platform for empowering the academic community at Universitas Negeri Gorontalo. Through the involvement of students in project planning, implementation, and supervision, this initiative reinforces the integration of theoretical knowledge and practical experience. The implementation methods include direct field observation, the preparation of detailed engineering designs (DED), and supervision reporting, all of which significantly contribute to the project's success. This article presents the outcomes of student involvement and its implications for enhancing academic capacity.